BOOK REVIEW: OWN YOUR OWN LIFE- By Richard G. Abell, M.D., Ph.D. and Corlis Wilber Abell. New York: Quick Silver Book, David Micky Company Inc 1976. Pp. 234. ISBN 978-0679506010 (Hardcover). 86.52. - Omaku, Sani A. S.; Tafida, Abubakar Musa; Zamani, Andrew E. (African Journal of Social and Behavioural Sciences, 2025)
"Own Your Own Life" is a comprehensive work authored by Richard G. Abell and Corlis Wilber Abell, aimed at psychotherapists, clients, and general readers. The genesis of this book stems from the authors’ personal experiences as well as their professional practices as clinicians. It is specifically designed for individuals seeking to achieve personal growth and for those dissatisfied with certain aspects of their lives who wish to enact change. The book encourages movement towards the existential perspective of “Personality Change." Individuals in need of transformation may find utility in therapeutic modalities such as transactional analysis, gestalt therapy, and nonverbal communication as instruments for their healing journey.